Клещи семейства Anoetidae (Sarcoptiformes) в гнездах грызунов и насекомоядных Закарпатья - Севастьянов, В.Д.; Высоцкая, С.О. (Вестник зоологии, 1971)
In the Transcarpathian region in nests of Microtus arvalis, Clethrionomys glareolus, Arvicola terrestris, Apodemus sylvaticus, A. flavicotus and in soil samples near nests seven species of mites were found from the family Anoetidae: Wichmannia spinifera, Mich . 1901 (in nests of all the rodent species), Wichmannia sp., hypopi of Histiostoma sapromysarum D u f. 1839, Histiostoma sp. and H. feroniarum D u f. 1839 (only in soil samples), nymphs of Myianoetus sp. Myianoetus microti sp. n. is described from the nests of Microtus arvalis. Hypopi of the new species differ from those of the known species in body proportions, other structure of sucking dist, equal sizes of propodosoma and hysterosoma setae.